1979
DOI: 10.1007/bf01808961
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of the coagulatory system in patients with severe cerebral trauma II.

Abstract: Platelet number, spontaneous aggregation, ADP- and adrenaline-induced aggregation, fibrinogen, and factors 2, 5, 7, and 10, were investigated in a series of 40 consecutive patients admitted to the clinic following severe head injury. Data were evaluated daily during the first week after trauma. Platelets were significantly decreased, particularly in non-survivors; there was no pathological spontaneous aggregation, except in a group of 22.5% of cases who had a mean age of 23.5 years. ADP-induced aggregation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

1979
1979
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…The disseminated intravascular thrombosis correlates strongly to ischemic damage and selective neuronal necrosis. Stein et al reported that intravascular microthrombi were detected in every section of frontal cortex and hippocampus in fatal TBI [1]. Graham et al supported those findings [9].…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The disseminated intravascular thrombosis correlates strongly to ischemic damage and selective neuronal necrosis. Stein et al reported that intravascular microthrombi were detected in every section of frontal cortex and hippocampus in fatal TBI [1]. Graham et al supported those findings [9].…”
Section: Discussionmentioning
confidence: 73%
“…However, the precise pathophysiological mechanism is still unclear. Several hypotheses have been proposed such as release of tissue thromboplastin by the injured brain, microthrombosis promoted by injured vessels and local hypercoagulation that leads to fibrinolysis [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cerebral ischemia is a hallmark of severe human TBI (Graham and Adams, 1971;Graham et al, 1989), as is coagulopathy (Goodnight et al, 1974;Auer and Ott, 1979;Kaufman and Mattson, 1985;Stein et al, 1992;Hoots, 1996). Traumatic coagulopathy is a form of disseminated intravascular coagulation (DIC), in which tissue thromboplastin is activated by injury (Ueda et al, 1985;Hoots, 1996;Gando et al, 1999).…”
Section: Introductionmentioning
confidence: 97%